The dynamics of quality growth in plums - Unuk, Tatjana (Anali PAZU, 2022)
At Fruit growing centre Maribor – Gačnik in 2010 we investigated the development of certain ripeness parameters for plum (Prunus domestica L.). The experiment included two varieties of plums: ´Valor´ and ´Hanita´. The aim of the experiment was to determine the optimal harvest time for each variety of plums and the connection between the dynamics of fruit skin colour development and the development of the taste (relationship between soluble solids content and acid content). The results showed that with different varieties of plum the colour as a quality and a ripeness parameter) is not a good indicator of the optimal harvest time, as with ´Valor´ the skin colour developed 17 days and with ´Hanita´ app. 14 days before it developed eating quality.
Keywords: plum; ripeness; colour; taste